Hybrid artificial intelligent systems : 12th International Conference, HAIS 2017, La Rioja, Spain, June 21-23, 2017, Proceedings /: 12th International Conference, HAIS 2017, La Rioja, Spain, June 21-23, 2017, Proceedings. (2017) - Unknown
No abstract available